Characteristics of water and heat changes in near-surface layers under influence of engineering interface. (October 2017) - Zhang, Zhongqiong; Wu, Qingbai; Liu, Yongzhi; Gao, Siru
Highlights: Hydrothermal difference variation was analyzed in the soil and air near the engineering surface. The main engineering interface influence scope in hydrothermal changes is calculated. The warming effect of the engineering interface on air and the underlying soil was evaluated. Abstract: The near-surface layer serves as a buffer layer in the discontinuous water–heat exchange between the atmosphere and soil. We analyzed the thermal regime and the water accumulation and mutation of the water–heat exchange based on the continuous in-situ water–heat monitoring data in air and soil from 2013 to 2014. The discontinuity scope was then divided. Results show that the surface temperature above the asphalt pavement was higher than the air temperature, except between November and January. The annual differences were 1.16 °C and 7.26 °C for the asphalt and sand pavements, respectively. The humidity above the asphalt pavement was 0.59 times that above the sand pavement. Therefore, asphalt pavement is not conducive to heat dissipation from soil to air. The heat absorption of the asphalt pavement is higher than that of the sand pavement. At the 5-cm depth, the soil heat flux under the asphalt pavement was 1.23 times that under the sand pavement. Meanwhile, high-aquifer layers with water mutations lay 5–30 cm beneath the pavement. According to the water–heat analysis and theoretical calculation, the interface influence scope changed by 2.55–3.29 mm and 28.2–46.44 cm above and below the asphalt pavement, and 2.9–4.31 mm and 15.8–43.6 cm above and below sand pavement. The water–heat change in the near-surface layer produces a warming effect on air and affects soil temperature. Therefore, design and maintenance engineering should pay attention to this layer in cold regions.